2007
DOI: 10.1681/asn.2007060642
|View full text |Cite
|
Sign up to set email alerts
|

Glial Cell–Derived Neurotrophic Factor–Independent Ureteric Bud Outgrowth from the Wolffian Duct

Abstract: The kidney collecting duct system and the ureter derive from the ureteric bud, an outgrowth of the Wolffian duct. It is generally believed that glial cell-derived neurotrophic factor (GDNF) plays a critical role in this earliest stage of kidney development, but 30 to 50% of knockout mice that lack either Gdnf or one of its receptors, such as Ret, have normal ureters. This suggests that an alternative pathway can induce ureteric bud outgrowth from the Wolffian duct. Isolated Wolffian ducts were cultured, and it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
64
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(69 citation statements)
references
References 30 publications
(31 reference statements)
5
64
0
Order By: Relevance
“…The recent detection of a GDNF bypass pathway, however, raises the possibility that even GDNF may not **This work performed by David Truong is currently unpublished. be essential for this step (51). Furthermore, a suspended culture system using a diluted Matrigel solution, in addition to the soluble growth factors, is required for the WD devoid of surrounding mesoderm to undergo in vitro budding.…”
Section: Discussionmentioning
confidence: 99%
“…The recent detection of a GDNF bypass pathway, however, raises the possibility that even GDNF may not **This work performed by David Truong is currently unpublished. be essential for this step (51). Furthermore, a suspended culture system using a diluted Matrigel solution, in addition to the soluble growth factors, is required for the WD devoid of surrounding mesoderm to undergo in vitro budding.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro and in vivo studies have revealed roles for members of fibroblast growth factor (FGF) family in primary ureteric budding. A combination of FGF7 and follistatin, an inhibitor of activin A, promotes supernumerary UBs from the WD in vitro, 16 and FGF10 alone has the same effect. 17 Genetic models support these results, because mice lacking either Fgf7, Fgf10, 18,19 or Fgfr2 deleted specifically in the ureteric epithelium 20 show renal hypoplasia.…”
mentioning
confidence: 96%
“…45 Recently, Maeshima et al showed that Fgf7, induced UB outgrowth in Ret null WDs when activin signaling was inhibited. 53 Conclusive evidence for participation of other RTKs in the network of Ret-Spry1 in the early events of WD growth to sculpt the metanephric kidney would require generation of multiple mutant alleles including Fgf pathway mutants, Spry1 and Ret signaling mutants.…”
Section: The Role Of Specific Ret-activated Pathways In Cakut Pathogementioning
confidence: 99%
“…Dr. Sanjay Nigam from UCSD has also shown that if you treat WD derived from Ret knockout animals with FGF7 in presence of inhibitors of activin you can actually induce UB outgrowth further supporting Fgf as an alternate pathway. 53 Jianghui Hou PhD, Assistant Professor of Medicine, Washington University School of Medicine: What is the biochemical basis for the RET signaling? It seems that RET activates PI3 kinase and MAPK kinase, but another kinase pathway upstream (SPRY1-raf) also activates MAPK.…”
Section: Questions and Answersmentioning
confidence: 99%